C-type Lectin Receptor Dectin-3 Mediates Trehalose 6,6′-Dimycolate (TDM)-induced Mincle Expression through CARD9/Bcl10/MALT1-dependent Nuclear Factor (NF)-κB Activation - Zhao, Xue-Qiang; Zhu, Le-Le; Chang, Qing; Jiang, Changying; You, Yun; Luo, Tianming; Jia, Xin-Ming; Lin, Xin (The Journal of biological chemistry, 2014)
Previous studies indicate that both Dectin-3 (also called MCL or Clec4d) and Mincle (also called Clec4e), two C-type lectin receptors, can recognize trehalose 6,6′-dimycolate (TDM), a cell wall component from mycobacteria, and induce potent innate immune responses. Interestingly, stimulation of Dectin-3 by TDM can also induce Mincle expression, which may enhance the host innate immune system to sense Mycobacterium infection. However, the mechanism by which Dectin-3 induces Mincle expression is not fully defined. Here, we show that TDM-induced Mincle expression is dependent on Dectin-3-mediated NF-κB, but not nuclear factor of activated T-cells (NFAT), activation, and Dectin-3 induces NF-κB activation through the CARD9-BCL10-MALT1 complex. We found that bone marrow-derived macrophages from Dectin-3-deficient mice were severely defective in the induction of Mincle expression in response to TDM stimulation. This defect is correlated with the failure of TDM-induced NF-κB activation in Dectin-3-deficient bone marrow-derived macrophages. Consistently, inhibition of NF-κB, but not NFAT, impaired TDM-induced Mincle expression, whereas NF-κB, but not NFAT, binds to the Mincle promoter. Dectin-3-mediated NF-κB activation is dependent on the CARD9-Bcl10-MALT1 complex. Finally, mice deficient for Dectin-3 or CARD9 produced much less proinflammatory cytokines and keyhole limpet hemocyanin (KLH)-specific antibodies after immunization with an adjuvant containing TDM. Overall, this study provides the mechanism by which Dectin-3 induces Mincle expression in response to Mycobacterium infection, which will have significant impact to improve adjuvant and design vaccine for antimicrobial infection.